PENGETAHUAN SIKAP DAN PERILAKU MASYARAKAT TERHADAP INSIDEN DEMAM BERDARAH DENGUE DI KELURAHAN BIAWA O, KELURAHAN LIMBA U.1 DAN KELURAHAN SIENDENG KECAMATAN KOTA SELATAN - Daud, Rustam K. (Jurnal Sainstek, 2010)
Peoples behavior of 2010 Health Indonesia expected is proactive to maintain and improve health in preventing incidence of disease, to protect our selves of threat of disease and to participate actively in movement of people effort. Therefore, it need knowledge of people early concerning danger of fever and effort of preventing this disease. Objective of this research was to know how do and to identify the Effect of Knowledge, Attitude, Behavior of Peoples on Dengue Haemorrhagic Fever at Sub District Biawa O, Limba U.1 and Siendeng District Kota Selatan City of Gorontalo.The research method that was used in this research was description with cross sectional study and with respondences 150 peoples. Data analyzed used variables stated by distribution of frequency either in absolute value or percentage in estimation using formulation of Machfoedz, I, (2004 : 15).For respondent of Sub District Biawa O, knowledge level has less category (54%), attitude level has less category (54,2%), and behavioral level in practice/action has less category (53%). For respondent of Sub District Limba U.1, knowledge level has less category (54,4%), attitude level has less category (54,3%), and behavioral level in practice/action has less category (54,4%). For respondent of Sub District Siendeng, knowledge level has good category (79,7%), attitude level has good category (94%), and behavioral level in practice/action has good category (80%). Knowledge, attitude, and behavioral of peoples at sub district Biawa O, Limba U.1 has less category and Siendeng has good category. Knowledge, attitude, behavioral of respondents had the effect on Dengue Haemorrhagic Fever Incident. Better knowledge, attitude and behavioral of respondents, lower chance of incident in this disease. Keywords : Dengue Haemorrhagic Fever, Educational Factor, Knowledge, Attitude and Behavior of Peoples